(untitled) (Estudios Gerenciales, 2014)
Small and medium-sized firms (SMEs) face serious challenges in order to be competitive, and they needto develop strategies enabling them to control their costs. This work aims to analyze and evaluate theimpact, penetration and characteristics of Activity-Based Costs (ABC). This research is of a quantitativetype descriptive design, with a sample of 180 SMEs. The results show low penetration of the ABC in SMEsusing traditional systems, due to the lack of knowledge, and that there are enterprises that do not use anycosting system at all. Finally the Mexican SMEs recognize the compatibility and usefulness of ABC, andthat the most important fact is to understand the possible application of different costing methodologiesfor different purposes.